URGENSI PEMAHAMAN TAHAPAN PENDIDIKAN FITRAH PERSFEKTIF FITRAH BASED EDUCATION KARYA HARRY SANTOSA: Pendidikan Fitrah - Andini Maesyaroh; Dewi Aryanti; Enung Hayati; Akhmad Fahrul SK (Fakultas Agama Islam Universitas Wiralodra, 2022)
THE URGENCY OF UNDERSTANDING THE STAGES OF FITRAH EDUCATION FROM THE PERSPECTIVE OF FITRAH BASED EDUCATION BY HARRY SANTOSA This discussion aims to explain the concept of nature and the understanding of teachers and parents in instilling natural education according to the age stages described in the book Fitrah Based Education and the urgency of understanding it among teachers and parents. This study uses a library research method, where the researcher analyzes the written literature as the main source and surveys the results of the t test on the understanding of nature to help researchers analyze the main source. The results of this study indicate that fitrah is a stage of education related to science and its implications in Islamic education that complement each other such as a puzzle leading to self-task based on the philosophy of life to be a servant to God (Allah) and to be part of humans in society as the embodiment of the purpose of life. and is related to the living system, namely the fitri religion, both of which construct morality and karimah which are then divided into 8 stages of nature, namely Faith Fitrah, Talent Fitrah, Learning Fitrah, Developmental Fitrah, Aesthetics and Language Fitrah, Individuality and Social Fitrah, Sexual and Love Fitrah, Fitrah Physical and Developmental Fitrah. This study analyzes the teacher's perspective on knowledge about nature education. eight were given to 59 respondents using a Likert scale. Teachers who participated in this study were asked to choose an understanding to see the extent of their understanding of nature education in general. The data were analyzed through the multi-faceted Rasch model. As a result, it was found that respondents did not understand nature education in detail, so an understanding of nature education was needed